Appraisal of Issues Affecting Soil-Steps Building for Sustainable Farmland Management in High Potential District, Ethiopia - Belay, Mehretie (Ethiopian Journal of Social Sciences, 2018)
Water caused soil degradation is a serious problem on farmlands in highland Ethiopia. Considerable investments in farmland conservation have been made to manage the problem in the past decades. However, the efforts have not been so pervasive to trim-down the danger to a desirable scale. This paper examines issues that impact application of soil-steps (bunds) as sustainable farmland management technology (SFLMT) by smallholder farmers in one of the high-potential production districts of northwest Ethiopia; Dangila woreda. Mixed method research designs involving concurrent acquisition and interpretation of quantitative and qualitative data were used in the study. Data were acquired from 201 randomly chosen  farming households during the harvest seasons of 2011 and 2012. Structured questionnaire survey, participatory field observation, key informant interview and focus group discussion were mechanisms employed during the data acquisition. Descriptive statistics (means, standard deviations and percentiles), Chi-square test, t-test and the binary logit model were in use to interpret the quantitative data. The qualitative information was textually narrated to augment the quantitative result. The findings of the investigation confirm that age of the household head, the number of household members, the slope of the farmland, the size of the farmland household held, the households’ participation in indigenous labour-sharing activities and the number of farm tools owned were significantly influenced by the building of soil-steps as SFLMT in the study district. Then again, taking part in off-farm activities and pest invasions were considerably hindering farmers from building soil-steps on their farms. In general, the results indicate that households’ access to livelihood material goods are key promoters for farmers’ implementation of soil-steps on their farmlands. Local resource conservation and development involvements should thus ponder on convalescing farmers’ material endowments to improve their capability to use soil-steps as SFLMT in their farming activities.